2022
DOI: 10.1186/s12866-022-02657-0
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and simultaneous detection of multiple pathogens in the lower reproductive tract during pregnancy based on loop-mediated isothermal amplification-microfluidic chip

Abstract: Background Female reproductive tract infection (RTI) is the common source of varied diseases, especially as an important risk factor for pregnancy outcomes, therefore the rapid, accurate and simultaneous detection of multiple pathogens is in urgent need for assisting the diagnosis and treatment of RTI in pregnant women. Streptococcus agalactiae (S. agalactiae), Enterococcus faecalis (E. faecalis), Gardnerella vaginalis (G. vaginalis), Candida albicans (C. albicans) and Chlamydia trachomatis (C.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…Following a thorough examination of the complete texts, an additional 16 studies were excluded as they did not align with the predefined selection criteria. Ultimately, this systematic review incorporated 12 studies [21][22][23][24][25][26][27][28][29][30][31][32], as illustrated in Figure 1. The characteristics of the studies encompassed in the analysis are detailed in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Following a thorough examination of the complete texts, an additional 16 studies were excluded as they did not align with the predefined selection criteria. Ultimately, this systematic review incorporated 12 studies [21][22][23][24][25][26][27][28][29][30][31][32], as illustrated in Figure 1. The characteristics of the studies encompassed in the analysis are detailed in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The PCR amplification of the ex-The genomic DNA of E. faecalis The characteristics of the studies encompassed in the analysis are detailed in Table 1. The publications incorporated in this review span the timeframe from 2009 [21] to 2022 [31,32].…”
Section: Growing Conditions Main Results Referencementioning
confidence: 99%
See 1 more Smart Citation
“…The development of a lab-on-chip (LOC) system based on the integration of LAMP and microfluidic technology is expected to speed the detection of pathogens and allow the early diagnosis of diseases (Figure 3). Currently, LAMP technology on LOC has been applied to the detection of breast cancer biomarkers, dengue serotypes, carbapenemase-producing organisms, and multiple pathogens in the lower reproductive tract during pregnancy (Moser et al, 2022;Wormald et al, 2022;Wu et al, 2022;Xu et al, 2022). Microfluidic chips are characterized by high throughput and low cost, a method of LAMP technology combined with a microfluidic chip to detect a Li et al 10.3389/fcimb.2022.1068015 variety of pathogens has been established, which can perform detection of multiple pathogens and real-time detection within 40 min without aerosol pollution and cross reaction (Ou et al, 2021).…”
Section: Lamp Combined With Microfluidic Technologymentioning
confidence: 99%
“…25,26 In recent years, the use of microfluidic chips has significantly enhanced the capabilities of LAMP assays by enabling high-throughput and simultaneous detection of multiple targets in a reagent-efficient and user-friendly manner. 27,28 Additionally, recent studies have demonstrated the successful application of LAMP assays in identifying T. vaginalis or HPV. 23,29 Hence, by combining LAMP and microfluidic technology, it becomes possible to achieve parallel and rapid detection of HPV and T. vaginalis, which can be instrumental in managing the risk of cervical cancer.…”
Section: Introductionmentioning
confidence: 99%